GEOSPATIAL ANALYSIS OF ROAD DISTRESSES AND THE RELATIONSHIP WITH THE SLOPE FACTOR - NOR A. M. NASIR; KHAIRUL N. A. MAULUD; NUR I.M. YUSOFF (Journal of Engineering Science and Technology, 2016)
A road is a medium that a person uses to move from one destination to another. A good road can provide comfort and safety to users, however, poor maintenance of a road might cause danger to them. Therefore, a road maintenance management system needs to be carried out to ensure the effectiveness as well as the efficiency of road maintenance itself. In this era, there are so many systems created in order to help data storage and analysis. One of the systems is the Geographic Information System (GIS). Other than getting the location of distresses, GIS also can help to classify the severity level of distresses and to correlate the distresses occurring in Universiti Kebangsaan Malaysia (UKM) with the slope gradient. Road distress data was collected using GPS applications supported by Supersurv 3 software. The study shows that the GIS method helps to produce a good spatial database. The road gradient factor is related to the level of road damage.